Mode of Information Delivery Does Not Effect Anesthesia Trainee Performance During Simulated Perioperative Pediatric Critical Events: A Trial of Paper Versus Electronic Cognitive Aids. Issue 6 (December 2016) - Watkins, Scott C.; Anders, Shilo; Clebone, Anna; Hughes, Elisabeth; Patel, Vikram; Zeigler, Laura; Shi, Yaping; Shotwell, Matthew S.; McEvoy, Matthew D.; Weinger, Matthew B.
Abstract : Introduction: Cognitive aids (CAs), including emergency manuals and checklists, have been recommended as a means to address the failure of healthcare providers to adhere to evidence-based standards of treatment during crisis situations. Unfortunately, users of CAs still commit errors, omit critical steps, fail to achieve perfect adherence to guidelines, and frequently choose to not use CA during both simulated and real crisis events. We sought to evaluate whether the mode in which a CA presents information (ie, paper vs. electronic) affects clinician performance during simulated critical events. Methods: In a prospective, randomized, controlled trial, anesthesia trainees managed simulated events under 1 of the following 3 conditions: (1) from memory alone (control), (2) with a paper CA, or (3) with an electronic version of the same CA. Management of the events was assessed using scenario-specific checklists. Mixed-effect regression models were used for analysis of overall checklist score and for elapsed time. Results: One hundred thirty-nine simulated events were observed and rated. Approximately, 1 of 3 trainees assigned to use a CA (electronic 29%, paper 36%) chose not to use it during the scenario. Compared with the control group (52%), the overall score was 6% higher in the paper CA group and 8% higher (95% confidence interval, 0.914.5; P = 0.03) in the electronic CA group. The difference between paper and electronic CA was not significant. There was a wide range in time to first use of the CA, but the time to task completion was not affected by CA use, nor did the time to CA use impact CA effectiveness as measured by performance. Conclusions: The format (paper or electronic) of the CA did not affect the impact of the CA on clinician performance in this study. Clinician compliance with the use of the CA was unaffected by format, suggesting that other factors may determine whether clinicians choose to use a CA or not. Time to use of the CA did not affect clinical performance, suggesting that it may not be when CAs are used but how they are used that determines their impact. The current study highlights the importance of not just familiarizing clinicians with the content of CA but also training clinicians in when and how to use an emergency CA. Abstract : Supplemental digital content is available in the text.